Autoregulation and repair in microtubule homeostasis. (February 2019) - Gasic, Ivana; Mitchison, Timothy J
Abstract : Even in the face of damaging insults, most cells maintain stability over time through multiple homeostatic pathways, including maintenance of the microtubule cytoskeleton that is fundamental to numerous cellular processes. The dynamic instability—perpetual growth and shrinkage—is the best-known microtubule regulatory pathway, which allows rapid rebuilding of the microtubule cytoskeleton in response to internal or external cues. Much less investigated is homeostatic regulation through availability of α-β tubulin heterodimers—microtubules' main building blocks—which influences total mass and dynamic behavior of microtubules. Finally, the most recently discovered is microtubule homeostasis through self-repair, where new GTP-bound tubulin heterodimers replace the lost ones in the microtubule lattice. In this review we try to integrate our current knowledge on how dynamic instability, regulation of tubulin mass, and self-repair work together to achieve microtubule homeostasis.